The Regional Comprehensive Economic Partnership Agreement and Its Expected Effects on World Trade - Lisandra Flach; Hannah-Maria Hildenbrand; Feodora Teti (Intereconomics, 2021)
The Regional Comprehensive Economic Partnership agreement creates the world's largest free trade zone. The agreement has the potential to increase trade relations among its members and further promote the development of regional value chains in "Factory Asia". This article presents the topics included in the recently concluded agreement, details the existing economic linkages between its members and discusses the expected consequences for its member states and third countries.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Freihandelsabkommen